Application of diverse FACTS in AGC of multi-area interconnected energy systems - Gulshan Sharma; Kabulo Loji; Musasa Kabeya (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This article presents the simple and effective control design for active power regulation of modern energy delivery system. As an energy delivery system experiences the demand changes as per the demand of the modern energy users due to which the system frequency is highly troubled and fluctuating. To balance such demand changes and to stable the system occurrence fluctuations, the thyristor control phase shifter (TCPS) in synchronisation with super conducting magnetic energy storage (SMES) or TCPS in coordination with capacitive energy storage (CES) based model predictive control (MPC) technique are proposed. SMES-SMES and CES-CES configurations are also tested for energy delivery system. The effectiveness of the proposed system regulator design are guaranteed by analyzing the transient system performance under varying load pattern, sinusoidal load change and for system non-linearities. A comparative performance analysis between TCPS-SMES, TCPS-CES, SMES-SMES and CES-CES based MPC of energy system are tested and presented.